2021
DOI: 10.3389/finsc.2021.696179
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of Three Odorant-Binding Protein Genes in the Foreleg Gustatory Sensilla of Swallowtail Butterfly Visualized by Multicolor FISH Analysis

Abstract: Lepidopteran insects are mostly monophagous or oligophagous. Female butterflies distinguish their host plants by detecting a combination of specific phytochemicals through the gustatory sensilla densely distributed on their foreleg tarsi, thereby ensuring oviposition on appropriate host plants. In this study, to gain insight into the molecular mechanism underlying host plant recognition by the gustatory sensilla, using Asian swallowtail, Papilio xuthus, we focused on a family of small soluble ligand-binding mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 54 publications
0
13
1
Order By: Relevance
“…In the annotation of OBPs, a novel OBP phylogenetically close to the PBP/GOBPs clade was identified as a partial gene PxutPBP5. In previous studies, 23,25 this gene was not found but presented in our current analyses. Unfortunately, this fragmented PxutPBP5 was unable to be extended to a fulllength sequence based on genomic and transcriptomic data.…”
Section: Discussioncontrasting
confidence: 49%
See 4 more Smart Citations
“…In the annotation of OBPs, a novel OBP phylogenetically close to the PBP/GOBPs clade was identified as a partial gene PxutPBP5. In previous studies, 23,25 this gene was not found but presented in our current analyses. Unfortunately, this fragmented PxutPBP5 was unable to be extended to a fulllength sequence based on genomic and transcriptomic data.…”
Section: Discussioncontrasting
confidence: 49%
“…26,28 In previous studies, the OBP gene family in P. xuthus was identified based on the genome and transcriptomes. 23,25 However, functional characterization of OBPs in this species is still unknown. Our current work comprehensively reannotated the OBP gene repertoire in P. xuthus, leading to the identification of four novel genes and the revision of seven original genes, in combination with two genome assemblies and extensive transcriptome data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations